The genomes of the most diverse AA genome rice species provide a resource for rice improvement and studies of rice evolution and domestication - Muhammad Abdullah; Agnelo Furtado; Ardashir Kharabian Masouleh; Pauline Okemo; Robert Henry (BMC Genomics)
Abstract Rice (Oryza sativa) is a staple food crop globally, with origins in wild progenitors within the AA genome group of Oryza species. Oryza rufipogon and Oryza meridionalis are native to tropical Asia and Northern Australia and offer unique genetic reservoirs. Here we explored the relationships of the genomes of these wild rice species with the domesticated rice genome. We utilized long read sequencing (PacBio HiFi) and chromatin mapping (Hi-C) to produce de novo chromosomal level genomes of Oryza meridionalis, the most divergent AA gnome species, and the unique Australian Oryza rufipogon like taxon that is a sister to the clade of domesticated and wild AA genome rice species of Asia and Africa. Comparative genomic analyses were conducted to identify structural variations and syntenic relationships between these wild taxa and the domesticated rice variety Nipponbare. The genome assemblies of the wild rice species achieved high completeness and contiguity, revealing the shared and unique genes in each species. Both wild species uniquely shared some genes with domesticated rice many of which were associated with disease resistance and stress tolerance. Structural differences included the large 6 Mb inversion on chromosome 6 specific to Japonica rice. Functional annotation highlighted conserved biological functions and novel genes unique to the wild taxa. These findings provide a deeper understanding of rice domestication and highlight the genetic contributions of wild species to enhancing the genetic diversity and ecological adaptability of modern rice varieties. Our study emphasizes the importance of conserving wild rice populations as genetic resources for breeding and adaptation in changing environments.